Its not all about sprinting: mechanisms of acute hamstring strain injuries in professional male rugby union—a systematic visual video analysis - Kerin, F.; Farrell, G.; Tierney, P.; McCarthy Persson, U.; De Vito, G.; Delahunt, E. (British Journal of Sports Medicine, 2022)
Objectives: The mechanisms of hamstring strain injuries (HSIs) in professional Rugby Union are not well understood. The aim of this study was to describe the mechanisms of HSIs in male professional Rugby Union players using video analysis.